Predator-prey transmission of a gammaherpesvirus from Asian badgers (Meles leucurus) to endangered Amur tigers (Panthera tigris altaica). - Martin Gilbert; Malcolm A M Hill; Leah Y N Cheung; Patti K Kiser; Ivan V Seryodkin; Dale G Miquelle; John M Goodrich; Nadezhda Sulikhan; Olga Uphyrkina; Mikhail Goncharuk; Linda Kerley; Ryan M Troyer (PLoS ONE)
We sought to identify herpesviruses in wild Amur tigers (Panthera tigris altaica) of the Russian Far East in and near the Sikhote-Alin Biosphere Zapovednik protected area. We used multiple herpesvirus consensus PCRs targeting the glycoprotein B and DNA polymerase genes followed by DNA sequencing to test blood samples collected over a 22-year period. We found identical herpesvirus sequences in 3 of 41 tigers by consensus PCR and 8 of 41 tigers (19.5%) using a virus-specific PCR. Persistent infection was demonstrated in a tiger that remained virus DNA-positive in three blood samples over a 2.5-year period. Surprisingly, the viral DNA sequence present in tigers had 98.8% identity to mustelid gammaherpesvirus 1 (MusGHV1) commonly found in European badgers (Meles meles), which do not range to the Russian Far East. We then tested 69 blood samples from 11 other carnivore species collected in this region and found that 81.0% (17/21) of Asian badgers (Meles leucurus), but no other species, had MusGHV1 sequences with 99.8-100% identity to those found in tigers. Interaction between Amur tigers and Asian badgers is supported by previous studies demonstrating that badgers are a common prey species for tigers in this region. Taken together, these results are consistent with the interpretation that a strain of MusGHV1 common in Asian badgers was transmitted via predator-prey interactions to Amur tigers. While gammaherpesviruses are generally thought to exhibit strong host species-specificity, our results present an example of cross-species transmission and one of the first examples, to our knowledge, of gammaherpesvirus predator-prey transmission. In addition, we identified novel gammaherpesviruses in sable (Martes zibellina), Asiatic black bear (Ursus thibetanus), and brown bear (Ursus arctos).